Comparative evaluation of the differential staining ability of carbol fuchsin, methylene blue, and turmeric GC-MI paste between enamel and adhesive composite remnant after orthodontic debonding using a spectrophotometer - Sunil Agrawal; Megha Jain; Achint Chachada (Wolters Kluwer Medknow Publications, 2024)
Background: After debonding, the primary concern of the clinician is to ensure the complete removal of the orthodontic adhesive composite remnant and restore the tooth surface to as near its original state as possible. However, the color resemblance of composite adhesive and enamel can increase the risk of tooth damage during debonding. To delineate composite from enamel, using various hydrophobic stains can be helpful in clean debonding. Objective: The aim of the present research was to assess and compare the differential staining ability of three stains, i.e., carbol fuchsin, methylene blue, and turmeric GC-MI paste, using a spectrophotometer. Methodology: A total of 48 premolar samples were distributed among three groups, namely, Group A, Group B, and Group C. Each group of 16 samples was stained with carbol fuchsin, methylene blue, and turmeric GC-MI paste, respectively. The color value of enamel and composite was measured before and after staining by digital spectrophotometer using CIE L* a* b* scoring method. Results: The mean difference color value of composite and enamel before and after staining was found to be 38.473 ∆ E, 17.211 ∆ E, and 18.715 ∆ E and 1.647 ∆ E, 1.297 ∆ E, and 1.293 ∆ E in Groups A, B, and C, respectively. The mean color value of composite and enamel was compared before and after staining using a t-test for all three groups and was found to be statistically highly significant. Conclusion: Carbol fuchsin, methylene blue, and turmeric GC-MI paste have the potential to be used as composite disclosing agents. Turmeric GC-MI paste appears to be a better agent as it stains composite effectively without significant staining on enamel.